Prevalence of Pyricularia orvzae cav. races in Rio Grande do Sul - Ribeiro, Alceu Sallaberry (Pesquisa Agropecuaria Brasileira, 2014)
A study was carried out with 124 isolares of the rice blast fungus (Pyricularia oryzae Cav.) which were obtained from 1969 to 1978 in order to determine the degree of variability within the fungus and study the occurrence and prevalence of physiologic races over the years. Based on reaction of the international rice differentials, 26 races were identified: IA-1, IA-5, IA-69, IA-85, IB-1, IB-5, IB-13, IB-21, IB-29, IB-37, IB-54, IB-63, IC-1, IC-5, IC-13, IC-21, IC-29, ID-5, ID-13, ID-16, IE-5, IF-1, IG-1, IG-2, IH-1 and II-1. Sub-races were registered in more than one isolate using additional set of local cultivars. The races IG-1, II-1, IH-1, IG-2, lA-5, IB-5 and IE-5 were more often encountered in the samples. However, the IG, IH, II and IB race groups were observed to be more frequent during 1969/1978. The physiologic races which were identified in this study showed some relationship with cultivars from which they were isolated. The existing races were found distributed all over the state. The disease reactions of the local rice cultivars to the rice blast were similar to the races of different groups, indicating, thereby, some pathogenic stability of the conidial population of P. oryzae in the environmental conditions of Rio Grande do Sul.